FINANCIAL PERFORMANCE ANALYSIS USING SOLVABILITY RATIO AT PT. SUPARMA TBK YEAR 2022-2023 - Dedali, Shindu (Universitas Maarif Hasyim Latif, 2024)
ABSTRACT The purpose of this research is to view and analyze the financial performance of PT. Suparma Tbk which looks at the Solvency Factor using the Debt to Equity Ratio & Debt Ratio, 2022-2023. This research is Quantitative Descriptive. This research data was obtained from the Financial Report of PT. Suparma Tbk in 2022-2023. Data is analyzed using the Solvency Ratio, namely the Debt to Equity Ratio & Debt Ratio. For the purpose of making this research, it looks at. The financial performance of PT. Suparma Tbk which looks at the Solvency factor using the Debt to Equity Ratio & Debt Ratio, in 2022 and 2023 in a Healthy condition and 2) The financial performance of Suparma Tbk, which looks at Solvency using the Debt to Equity Ratio & Debt Ratio, in 2022 and 2023 is in good condition. And the results show that the Debt to Equity Ratio & Debt Ratio for 2022-2023 has good performance, so that the Management of PT. Suparma Tbk can pay debts so that the Company can run its business. Keywords: Financial Performance, Debt to Equity Ratio & Debt Ratio